Introducing the Levantine Ceramics Project - Berlin, Andrea M. (Journal of Hellenistic Pottery and Material Culture, 2021)
The Levantine Ceramics Project (LCP; www.levantineceramics.org) is a new model for communicating, linking, and expanding the use of ceramic data. The LCP is a public, crowd-sourced web application focused on ceramics produced anywhere in the Levant, meaning the modern countries of Turkey, Syria, Cyprus, Lebanon, Israel, Jordan, and Egypt, from the beginnings of ceramic production in the Neolithic era (c. 5500 BCE) through the time of the Ottoman Empire (c. 1920 CE).